The Patronage of Doña Francisca de Cáceres in Her Chapel at the Church of La Trinidad (Segovia, 1511): Interpreting Archival Sources in Secondary Education - Contreras Jiménez, María Eugenia (Educación y Futuro: Revista de Investigación Aplicada y Experiencias Educativas, 2024)
This case study examines the patronage of a Castilian widow in the early 16th century, offering secondary level students an approach to under-standing the significance of historical knowledge sources, scholarly tradi-tion —shaped by the writer’s historical context— and women’s history methodologies. the principal elements of Doña Francisca de Cáceres’ per-sonal and social identity have emerged; she was a member of Segovia’s urban oligarchy and commissioned an altarpiece in 1511 for her funeral chapel in the city’s church of la Trinidad.